New Brazilian pilgrimages and their interfaces with tourism - Carneiro, Sandra Maria Corrêa de Sá (2004)
In this paper I intend to focus on the “creation”, or “recreation”, of new pilgrimage routes within the Brazilian context, and their relation to tourism. I, hereby, analyze five routes, known as “Caminho do Sol (Sunshine Route), Caminho da Luz ( The Light Route), Caminho das Missões (The Missions’ Route), Passos de Anchieta (Anchieta’s Steps) and “Caminho da Fé” (The Faith Route), in the states of São Paulo, Minas Gerais, Rio Grande do Sul, Espírito Santo. All of them are Brazilian “Inventions” based on the model of “Santiago of Compostela Trail” The whole research is based on the assumption that both pilgrimage and tourism can be understood as structures of significance, both pointing to the different possible ways of experiencing such practices and to a diverse range of possible transformations. I understand that the main difference between these two structures of significance (tourism and pilgrimage) lies both on the external character of the sight and on the degree of immersion of the participants of each type of experience.